2017
DOI: 10.1242/jcs.196865
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis homolog of Scc4/MAU2 is essential for embryogenesis

Abstract: Factors regulating dynamics of chromatin structure have direct impact on expression of genetic information. Cohesin is a multi-subunit protein complex that is crucial for pairing sister chromatids during cell division, DNA repair and regulation of gene transcription and silencing. In non-plant species, cohesin is loaded on chromatin by the Scc2-Scc4 complex (also known as the NIBPL-MAU2 complex). Here, we identify the Arabidopsis homolog of Scc4, which we denote Arabidopsis thaliana (At)SCC4, and show that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 62 publications
4
25
0
Order By: Relevance
“…In Arabidopsis (Arabidopsis thaliana), the scc4 mutation leads to endosperm defects and embryo lethality, similar to the effects of the scc2, smc1, and smc3 mutations (Liu Cm et al, 2002;Sebastian et al, 2009;Minina et al, 2017). SCC4 depletion leads to precocious sister chromatid separation (PSCS) during mitosis in yeast and animals (Ciosk et al, 2000;Seitan et al, 2006;Watrin et al, 2006); however, the function of SCC4 in plant cell mitosis remains unclear.…”
Section: Introductionmentioning
confidence: 96%
“…In Arabidopsis (Arabidopsis thaliana), the scc4 mutation leads to endosperm defects and embryo lethality, similar to the effects of the scc2, smc1, and smc3 mutations (Liu Cm et al, 2002;Sebastian et al, 2009;Minina et al, 2017). SCC4 depletion leads to precocious sister chromatid separation (PSCS) during mitosis in yeast and animals (Ciosk et al, 2000;Seitan et al, 2006;Watrin et al, 2006); however, the function of SCC4 in plant cell mitosis remains unclear.…”
Section: Introductionmentioning
confidence: 96%
“…The predicted protein sequence of Arabidopsis SCC2 reveals a putative plant homeodomain (PHD) finger, a domain involved in chromatin organization and regulation of gene expression (Sebastian et al, 2009). Cytological analyses of T-DNA insertional lines Atscc2-2 , Atscc2-3 , Atscc4-1 and Atscc4-1 indicates that in these lines 25% of all embryos develop only up to the heart stage and show loss of bilateral symmetry, cell over-proliferation in the suspensor, and in the case of Atscc2-2 , over-proliferation of the endosperm (Minina et al, 2017). In Atscc4-1 and Atssc2-2 analysis of the distribution of the auxin-response reporter DR5rev::3xVENUS-N7 indicates that most of the reporter is confined to the basal cells of the suspensor, which is the opposite to the wild type, suggesting the existence of: (a) alterations in the embryogenic potential of the suspensor in the mutants, and (b) a role for both SCC4 and SCC2 in embryonic cell fate determination (Minina et al, 2017).…”
Section: Loading Of the Cohesin Complexmentioning
confidence: 99%
“…Cytological analyses of T-DNA insertional lines Atscc2-2 , Atscc2-3 , Atscc4-1 and Atscc4-1 indicates that in these lines 25% of all embryos develop only up to the heart stage and show loss of bilateral symmetry, cell over-proliferation in the suspensor, and in the case of Atscc2-2 , over-proliferation of the endosperm (Minina et al, 2017). In Atscc4-1 and Atssc2-2 analysis of the distribution of the auxin-response reporter DR5rev::3xVENUS-N7 indicates that most of the reporter is confined to the basal cells of the suspensor, which is the opposite to the wild type, suggesting the existence of: (a) alterations in the embryogenic potential of the suspensor in the mutants, and (b) a role for both SCC4 and SCC2 in embryonic cell fate determination (Minina et al, 2017). It was also found that SCC4 interacts stably with the N-terminus of SCC2 in planta and in baker’s yeast, but this interaction is not required for proper localization of SCC4 to the plant nucleus in Atscc2-2 (Minina et al, 2017).…”
Section: Loading Of the Cohesin Complexmentioning
confidence: 99%
See 2 more Smart Citations